Análise qualitativa comparativa do uso do gadolínio em exames de ressonância magnética de crânio - Wolter, Brenda von (2023)
Gadolinium is the contrast agent most used in MRI exams. It can be divided into macrocyclic agents, more stable, and linear agents, less stable due to ion release. This work aimed to investigate two gadolinium-based contrast media, Omniscan (linear) and Gadovist (macrocyclic), and their deposition in the body of patients undergoing magnetic resonance imaging. Thus, a review of the main articles on the topic was carried out, as well as a comparative analysis of images. Images from 60 skull MRI exams that patients underwent as part of their routine were analyzed, which were subdivided by areas in exams with clinical indication for the tumor, era and pituitary protocol, and which already used contrast within the institution’s protocol. There was also a division between 30 patients who received 15 ml of Omniscan contrast and 30 patients who received 5 ml of Gadovist contrast. For this, the image quality and contrast impregnation in the Axial T1 Fat Sat 3D FSPGR GD sequence of each exam were considered, observing the following structures: internal jugular vein, internal carotid artery, pituitary gland, right and left middle cerebral arteries and finally the transverse sinuses and the sagittal venous sinus. The visual and comparative analysis of the images was carried out by the researcher and the diagnoses and reports were given by the same radiologist at the institution. As a result, it was possible to observe that there was no loss in the images that were acquired with lower doses of contrast. Gadovist showed tissue impregnation and differentiation in the same way as Omniscan, but due to its molar concentration it was possible to use a more optimized and safer dose for the patient.